Implikasi Hukum Kebijakan Food Estate Di Kawasan Hutan Terhadap Kelestarian Ekosistem Hutan - Amelia Zulfitri (Nagari Law Review, 2025)
The Food Estate policy implemented in forest areas is part of Indonesia’s efforts to improve national food security; however, its implementation has the potential to undermine the sustainability of forest ecosystems. A key issue concerns the conversion of forest areas into large-scale agricultural land, leading to deforestation, loss of biodiversity, and disruption of hydrological cycles that may contribute to global climate change. This study aims to examine various legal issues arising from the implementation of this policy, particularly those related to the regulation of natural resource conservation and efforts to maintain forest ecosystem sustainability. This study employs a normative juridical approach by analyzing relevant statutory provisions and examining the extent to which food security policies align with or conflict with environmental conservation principles. The findings reveal that the implementation of the Food Estate policy has not yet fully aligned with conservation principles stipulated in existing legislation, including provisions contained in the Law on the Conservation of Biological Natural Resources and Their Ecosystems. Therefore, more comprehensive environmental impact assessments and meaningful public participation at every stage of policy implementation are necessary to ensure a balance between food security and forest sustainability.